EVALUATION OF VAT COLLECTION ON TRADING THROUGH ELECTRONIC SYSTEM - Kusumabangsa, Gilang (UI Scholars Hub, 2021)
This research aims to evaluate the Value-added Tax (VAT) collection on trading through the electronic system (TTES) from the TTES VAT Collector’s perception, based on